COCRIAÇÃO DE VALOR NO RELACIONAMENTO ENTRE EMPRESA E CLIENTE: UM ESTUDO NA EMPRESA MERCUR E SEU MODELO DE INTERAÇÃO - Severo Lima, Camila (2022)
This study seeks to understand the role of value co-creation in the context of relationship between company and customer. It analyzed and identified the relationship strategies based on co-creation and understood the relational gains arising from this process. The study was carried out through exploratory qualitative research, using a single case study, in the company Mercur S.A., from the application of semi-structured interviews with three different audiences: employees, customers and graduate students who have a relationship with the theme. Through the analysis of collected data and relations with theory, it is understood that co-creation improves the relationship that the company has with the customer. The company works from the notions of DART model, proposed by Prahalad and Ramaswamy (2004a), in which there is dialogue, access, risks and benefits and transparency. The research brought significant gains in relation to the study of co-creation, such as learning and the risks involved in this process, which can serve as an inspiration for other companies. It is suggested that be applied a survey that can measure the value co-created with various stakeholders in order to identify and, therefore, deepen it as a strategic advantage for the company. It is also understood that it is important to develop new studies that relate value co-creation with the creation of shared value.